Implementasi Kebijakan Penyelesaian Pelanggaran Administratif Pemilihan Umum Kabupaten Banyuasin - Zuber, Konar; Zulkifli, Zulkifli; Berlian, Ong (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
The implementation of the Policy for the Settlement of Administrative Violations in the Banyuasin Regency General Election is in the good category, this is because for each indicator such as the media for disseminating information from the policy for the Settlement of Administrative Violations in the Banyuasin Regency General Election, it is disseminated to the sub-districts (Panwaslu) in Banyuasin Regency through the Commissioner, staff or employees in the Bawaslu of Banyuasin Regency, either through coaching, technical guidance and coordination meetings between the Chair/Members of Panwaslu, staff or employees handling violations committed at Bawaslu of Banyuasin Regency, regarding the clarity of the information that has been conveyed is clear enough, as well as the implementation of coaching and strengthening capacity of HR or staff in terms of resolving administrative violations that are always being carried out For disposition which includes the capabilities possessed by the Commissioner, staff and Panwascam in the Bawaslu ranks of Banyuasin Regency k if according to my observations it is quite good, this can be seen from the educational qualifications they have, according to the fields and disciplines they have, and are qualified based on the experience they have, and they often follow technical guidance, coordination meetings, as a form of strengthening capacity as an election organizer, and most importantly the process of handling these violations is in accordance with the mechanism for handling violations in Perbawaslu 8 of 2018 concerning technical handling of administrative violations.